Immunoregulation in experimental filariasis. IV. Induction of non-specific suppression following in vitro exposure of spleen cells from infected jirds to Brugia pahangi antigen. - Lammie, P J (1984)
Studies with inbred jirds chronically infected (greater than 5 months) with Brugia pahangi have demonstrated splenic suppressor cells which modulate in vitro responsiveness to mitogens and parasite antigens. The stimuli which induce suppression were characterized by analysing the effect of activated cells from inbred normal or B. pahangi-infected jirds on the PHA and PWM responsiveness of cultures on normal cells. Regulatory cells were stimulated in vitro with concanavalin A (Con A; 5 micrograms/ml) or an extract of adult B. pahangi (20 micrograms/ml) for 72 hr and irradiated (1500 rads) prior to cocultivation with normal cells. Addition of Con A-activated normal spleen cells to normal cells produced moderate suppression of PHA and enhancement of PWM responsiveness. However, Con A-stimulated spleen cells from infected animals consistently suppressed both the PHA and PWM responsiveness of normal cells by 80-90%. Spleen cells from chronically infected jirds were also induced by B. pahangi antigen to suppress both the PHA and PWM responsiveness of normal lymphocytes. In contrast, spleen cells from animals 3-15 weeks after infection and lymph node cells from all time points were capable of suppressing only PWM responses when stimulated by antigen. Normal spleen cells were not induced by B. pahangi antigens to exhibit immunoregulatory activity. The suppression mediated by antigen-induced spleen cells from chronically infected jirds was partially or totally alleviated by removal of non-specific suppressor cells which are plastic adherent and cyclophosphamide-sensitive, or by removal of antigen-specific suppressor cells which bear receptors for histamine. the results suggest the involvement of regulatory cell circuits in experimental filarial infections.